The petrochemistry of metabasites from a precambrian amphibolite-granulite transition zone, South Norway - Clough, Peter W. L. (1977)
The metabasites of the Arendal~Tvedestrand district were originally minor igneous intrusions, but are now characterised by wholly metamorphic mineral assemblages and textures, which are diagnostic of a prograde amphibolite-granulite facies transition. The main mineralogical changes with increasing grade of metamorphism (zone A to zone C) are decreases in modal hornblende and biotite, with increased pyroxenes. Major and trace element analyses for 176 metabasites are presented, and show the overall chemistry to be analogous to that of basaltic rocks. K and Rb vary systematically across the transition zone, declining in abundance with increased grade of metamorphism. In other respects, zones A and B are chemically homogeneous. Zone C (Tromloy) metabasites are characterised by low Ti02, K20, P205, H20, Zr, Ni, Sr, Ba, Rb, and high Na20, (MnO) , Zn, and oxidation ratios relative to the mainland suite. In part, these abundances are related to an original igneous fractionation in which a fairly strong iron-enrichment was accompanied by increased levels of Ti02, P205 and 'incompatible' elements, and decreases in transition trace elements. The relative absence of iron-rich differentiates in zone C accounts for the lower levels of P205 and Ti02 in this zone. Secondary fractionation accompanied the metamorphism, and resulted in K and Rb redistribution throughout the terrain and the Na20 enhancement in zone C. Ba, Sr and Zr appear to be depleted in this zone. These chemical changes are also noted in the acid- intermediate charn-ockitic suite of the transition zone, which is genetically distinct from the metabasites. 'Stable' element discrimination diagrams, ( when used with caution in view of these fractionation patterns) show the suite to be originally tholeiitic. Preliminary microprobe data support the concept of chemical equilibrium in the metabasites. Almandine-rich garnets are sporadically developed in the suite, and their growth is not directly related to the host-rock chemistry.